The Effect of Leucaena leucocephala Supplementation on Performance and Gastrointestinal Helminths Control in Kacang Goats (Capra aegagrus hircus) - Evi Warintan Saragih; Jhon A. Palulungan; Purwaningsih Purwaningsih; Noviyanti Noviyanti (Animal Husbandry Department, The Faculty of Agriculture, Universitas Syiah Kuala, 2026)
Goat productivity in Indonesia is often constrained by low-quality forage diets and a high prevalence of gastrointestinal parasitic infections, leading to significant economic losses. This study investigated the effects of Leucaena leucocephala supplementation on feed intake, weight gain, and gastrointestinal helminth control in Kacang goats. Using a latin square design, nine goats were assigned to three treatments: P1 (0%), P2 (20%), and P3 (40%) Leucaena leucocephala inclusion in a forage mix of Pennisetum purpuphoides and Gliricidia sepium. The measured variables included daily feed intake, weekly weight gain, and fecal egg counts (FECs). Supplementation significantly (P<0.05) increased the average daily feed intake from 0.89±0.10 kg (P1) to 1.86±0.31 kg (P2) and 1.81±0.37 kg (P3). Growth performance improved markedly, with the P3 group achieving the highest weekly weight gain of 1.08±0.27 kg (154.76 g/day), which was significantly higher than that of the control group. Furthermore, L. leucocephala inclusion led to a substantial reduction in parasite burden; FECs decreased from 290±96.02 EPG (P1) to 190±76.55 EPG (P2) and 140±52.92 EPG (P3). Supplementation at the 40% level reduced helminth infection by approximately 51.7% compared with the control diet. In conclusion, L. leucocephala serves as both a high-quality nutrient source and a functional anthelmintic agent. Although a 20% inclusion rate is sufficient to optimize growth performance, the 40% level provides a superior reduction in gastrointestinal parasite burdens.